The Larvae of European Ascalaphidae (Neuroptera) - Badano, Davide; Pantaleoni, Roberto Antonio (Zootaxa, 2014)
The larvae of all the European genera of Ascalaphidae are compared for the first time, highlighting the differential characters for identification purposes. The larva of the genus Ascalaphus is described for the first time while those of Puer, Bubopsis and Deleproctophylla are deeply revised. Actually, the larvae of Ascalaphus festivus (Rambur), Puer maculatus (Olivier), Bubopsis agrionoides (Rambur), Deleproctophylla australis (Rambur), Libelloides latinus (Lefebvre), Libelloides corsicus (Rambur) and Libelloides siculus (Angelini) are described or accurately depicted for the first time. The known larvae of the genus Libelloides are reviewed.